Institute of parties as main participants of economic trial - Первушина, А. А.; Хатнюк, Н. С. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Investigation theoretical aspects of institute of parties as main participants of economic trial, in particularproblems of terminology determination and interpretation of concept «party» as a main participant ofeconomic trial, «claimant» and «defendant», as parties of economic trial, and also characteristic featureswhich must to be allotted by the subject of menage for acquisition judicial status of party of economic trial.On the basis of the got conclusions the improvement of determination of parties is offered as mainparticipants of economic trial.